Transparent glass-ceramic waveguides made by femtosecond laser writing. (April 2021) - Ferreira, P.H.D.; Fabris, D.C.N.; Villas Boas, M.O.C.; Bezerra, I.G.; Mendonça, C.R.; Zanotto, E.D.
Highlights: Fabrication of waveguides in Transparent Glass-Ceramic (TGC) via fs-laser writing. Buried waveguides in Magnesium Aluminum Silicate (MAS) TGC and its precursor glass. Single mode (precursor glass) and ring mode (MAS-TGC) were obtained. Femtosecond laser writing technique. Strengthened photonic devices. Abstract: Transparent glass-ceramics (TGC) have been investigated to replace hard, mechanically strong, scratch resistant materials in ballistic armor applications and smart phone displays. Certain types of TGC have superior performance than borosilicate and soda-lime glasses, and are much easier to produce, especially large parts, than transparent mono or polycrystalline ceramics. Thereupon, transparent glass-ceramics could be feasible in other applications, such as stronger photonic devices. In this work, we used femtosecond laser pulses to inscribe optical waveguides inside a magnesium aluminum silicate (MAS) precursor glass and glass-ceramic, which has shown satisfactory mechanical properties to be applied as ballistic armor. Single mode waveguides for the precursor glass and ring mode for MAS-TGC were obtained and characterized (total insertion loss, mode profile, and threshold energy for heat diffusion at different fabrication depths). Micro-Raman measurements on the microfabricated waveguide core and on the pristine material surface show some difference for the TGC, but none for the glass. Particularly, we found that the threshold energy for heat diffusion is higher in the MAS glass-ceramic than in its parent glass. Its good optical waveguiding and mechanical properties indicate that this new TGC might be adequate for photonic devices that require mechanically competent materials.